Translation bootstrapping: a process-oriented shift analysis. - Ilkhanipour, Negin (Perspectives: Studies in Translatology, 2012)
One of the founding issues in translatology is shift analysis, already enriched with valuable product-oriented approaches. The present paper borrows the concept of bootstrapping from the field of bilingualism and applies it to a process-oriented analysis of translation shifts; so as to reach ‘translation bootstrapping’, a continuum with two extremes of function-reduced and function-embedded translations has been drawn making use of language functions. Each point on this continuum is related to other points through the notion of parallel distributed processing. An example of the translation of an English proverb into Persian and two figures have also been provided to make the abstraction tangible.